(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
National renaissance is a multifaceted process involving the revival of a nation’s cultural identity, social cohesion, political integrity, and economic prosperity. Central to this renaissance is the creation of an enlightened society—one that fosters knowledge, critical thinking, ethical values, and active civic engagement among its citizens. This article explores the fundamental requirements necessary to build such a society, focusing on comprehensive education, cultural preservation, social justice, and participatory governance. Drawing on global experiences and theoretical frameworks, the study provides a roadmap for policymakers and scholars aiming to facilitate sustainable national development through enlightenment.